Dari Syahadat ke Akhlak: Aktualisasi Rukun Islam dalam Kehidupan Sehari-hari Mahasiswa Muslim - Rapia kahri; Yaya Putri Syam; Herlina, Herlina; St. Nurhayati Ali (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The Pillars of Islam are the main foundation of Islamic teachings, encompassing the dimensions of faith, worship, and social life. However, in the context of the lives of Muslim students, the implementation of the pillars of Islam is often understood as merely ritualistic practices without appreciating the moral and social values ​​they contain. This article aims to comprehensively examine the actualization of the pillars of Islam—from the shahada to the hajj—in the formation of the morals and daily behavior of Muslim students through a literature study approach. The method used is a literature review of classic and contemporary books, scientific journal articles, and relevant documents discussing the pillars of Islam, moral education, and student character. The results of the study indicate that each pillar of Islam has direct implications for the development of student personality, such as the shahada, which strengthens identity and integrity, prayer, which fosters discipline and moral awareness, zakat, which fosters social awareness, fasting, which trains self-control, and the hajj, which instills the values ​​of brotherhood and equality. The holistic actualization of the pillars of Islam not only strengthens students' religiosity but also contributes to the formation of noble morals in academic and social settings. Therefore, integrative efforts in higher education are needed to foster an understanding of the pillars of Islam that goes beyond rituals and is internalized in the attitudes, ethics, and behavior of Muslim students in their daily lives.